IMPLEMENTATION OF 'VILLAGE FAMILY PLANNING ' PROGRAM IN RPTRA CIRACAS PRIMA, EAST JAKARTA - Okta Zenita Siti Fatimah; Dewi Suri Damayanti (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Some women did not know when they could get pregnant again. Choices in birth planning are very influential in preventing complications. This study was based on the launching of the Village family planning in RPTRA Ciracas Prima. The purpose of this study was to describe the implementation of the Village family planning in RPTRA Ciracas Prima. This study was qualitative with descriptive method — data collected by an in-depth interview by following the guidelines. The information obtained was recorded and made in the form of field notes a model on Policy Implementation developed by George C. Edward III. The results showed that the program in RPTRA Ciracas Prima based on four implementation indicators discovered that in communication, the transmission was carried out with an effort to socialize its clarity, which was not yet fully understood by the public. The bureaucratic structure and targets should be optimized. RPTRA had inadequate facility resources like a limited corridor, and particular medical space was incomplete. However, the last indicators showed from the optimization of cadre effort implementing the village family planning program. Population growth significantly increases know from the number of acceptors of long-acting reversible contraception. In the implementation of facilities and infrastructure such as Pos village family planning, it should be devoted to activities related to family planning. BKKBN must be able to motivate the community so that they can participate in the implementation of the village family planning program in RPTRA Ciracas Prima. Keyword: implementation, village family planning